THE EFFECT OF BRANDING AND PACKAGING ON PURCHASE DECISIONS IN UMKM CAHAYA RASA, WRINGINSONGO VILLAGE, MALANG REGENCY - Mahmudatul Himma; Fullchis Nurtjahjani; Diana Eka Poernamawati; Asminah Rachmi; Muhamad Muwidha; Ane Fany Novitasari (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study aims to analyze the influence of Branding and Packaging on consumer purchasing decisions. In an era of increasingly tight market competition, factors such as brand image and packaging design play an important role in attracting consumer attention and influencing purchasing decisions. This study uses a quantitative approach with a survey as a method of data collection. The population in this study were consumers of UMKM (Micro, Small, and Medium Enterprises) Cahaya Rasa, Wringinsongo Village, Malang Regency. The number of samples in this study was 180 people using a purposive sampling technique. The data collected will be analyzed using multiple linear regression. The results of the study show that Branding and Packaging have a significant role in influencing consumer purchasing decisions at UMKM Cahaya Rasa. The stronger the brand image that is built and the more attractive and informative the product packaging offered, the higher the likelihood of consumers making purchases.